Nickel-saving electrode for LNG storage tank

CN118513724BActive Publication Date: 2026-10-23KUSN GINTUNE WELDING
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410672553.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2026-10-23
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

现下国内9%Ni钢制LNG储罐应用最广泛、最成熟的ENiCrMo-6焊条并不能很好的与新研发的节镍型7%Ni钢板性能相匹配,主要就体现在板厚超过27mm厚度时,接头的耐气孔性和弯曲性能难以保障

Benefits of technology

[0044]1、低成本、低硬度、易加工的极低碳-低Mn-无Mo-Ni-Cr-Fe-含Ti/Nb镍铬铁焊芯,在优化焊芯的加工性、降低加工成本的同时,精准的合

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118513724B_ABST
    Figure CN118513724B_ABST
Patent Text Reader

Abstract

The application discloses a nickel-saving electric welding rod for LNG storage tank, which is composed of a welding core and a coating wrapped on the surface of the welding core, and the chemical components and their weight percentage contained in the welding core are as follows: C≤0.01%, Mn: 0.60-1.20%, Si: 0.08-0.24%, P≤0.005%, S≤0.003%, P+S≤0.006%, Ni: 62.0-77.5%, Cr: 18.0-24.0%, Fe: 2.0-10.0, Nb: 1.20-2.40%, Ti: 0.080-0.300%, and other impurity elements≤0.50%. In the case that the nickel-saving electric welding rod has equivalent mechanical properties to the conventional 9%Ni steel matched with ENiCrMo-6 welding rod, the nickel-saving electric welding rod has better adaptability to the newly developed 7%Ni steel for LNG storage tank in the market, and the porosity of the joint of the thick plate is extremely low, and the crack resistance is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of welding materials, and specifically relates to a nickel-saving welding electrode for LNG storage tanks. Background Technology

[0002] With the acceleration of global industrialization and informatization, the world's energy demand has increased dramatically. Natural gas (LNG), as a high-quality clean fuel and an important chemical raw material, has become one of the world's three pillar energy sources. 9% Ni steel is a medium-alloy, low-carbon, quenched and tempered steel with W(Ni)-9% developed by the International Nickel Company in the United States in 1944. This steel exhibits good toughness and high strength at extremely low temperatures, with a minimum operating temperature of -196℃. Compared to austenitic stainless steel and aluminum alloys, it has advantages such as a lower coefficient of thermal expansion and better economic efficiency. Since research in 1960 proved that it could be used safely without post-weld stress-relieving heat treatment, 9% Ni steel has become the main material used in the manufacture of large LNG storage tanks.

[0003] Currently, my country has achieved large-scale production of 9% Ni steel for LNG storage tanks, and the product quality has reached the international advanced level. However, my country still needs to import a large amount of steel every year to meet the needs of national economic development. Therefore, while ensuring product quality, reducing the construction cost of LNG storage tanks, improving the overall competitiveness of tank design and construction, and developing low-cost, nickel-saving steel for LNG storage tanks and supporting welding materials are urgently needed. Nickel-saving 7% Ni steel is a new type of cryogenic material for LNG storage tanks. Nanjing Iron & Steel Co., Ltd. (Nanjing Steel) has adopted a nickel-saving alloying design with 6-7% Ni and strengthened with elements such as Cr, Mo, and trace amounts of Nb. They have innovatively adopted a heat treatment process of "controlled rolling - ultra-fast cooling - sub-temperature quenching - tempering" to successfully develop nickel-saving 7% Ni steel for LNG storage tanks. Its mechanical properties are comparable to 9% Ni steel, reducing the material and manufacturing costs of LNG storage tank construction by 20% and 30% respectively, and is expected to achieve significant social and economic benefits.

[0004] The performance of 7% Ni steel plates used in nickel-saving LNG storage tanks is comparable to that of 9% Ni steel, but currently there are no matching welding materials. In LNG storage tank construction projects, plates thicker than 20mm are generally defined as large-thickness plates. As the capacity of LNG storage tanks increases, the thickness of the matching steel plates also increases, with 27mm, 32mm, 37mm, and even 42mm thick steel plates being widely used. With the increase in the thickness of the base steel plate, the restraint increases significantly, and the requirements for the crack resistance of the welding materials become higher. The gas escape from the weld accumulates with the increase in weld thickness corresponding to the plate thickness, and the requirements for the porosity resistance of the welding materials also increase. Currently, the most widely used and mature ENiCrMo-6 welding electrode for 9% Ni steel LNG storage tanks in China cannot be well matched with the performance of the newly developed nickel-saving 7% Ni steel plates, mainly because when the plate thickness exceeds 27mm, the porosity resistance and bending performance of the joint are difficult to guarantee. Summary of the Invention

[0005] To solve the above-mentioned technical problems, the present invention provides a new type of welding electrode for nickel-saving LNG storage tanks. While having comparable mechanical properties to the traditional 9% Ni steel ENiCrMo-6 welding electrode, it has better compatibility with 7% Ni steel for nickel-saving LNG storage tanks. It has excellent joint porosity resistance and bending performance for thick plate base materials, and the joint porosity of thick plate is extremely low and the crack resistance is better.

[0006] To achieve the above-mentioned technical objectives, the technical solution of the present invention is a nickel-saving welding electrode for LNG storage tanks, comprising a welding core and a flux coating. The flux coating is applied to the outer wall of the welding core. Based on the total weight of the welding core, the chemical composition and its weight percentage content of the welding core are as follows: C≤0.01%, Mn: 0.60~1.20%, Si: 0.08~0.24%, P≤0.005%, S≤0.003%, P+S≤0.006%; Ni: 62.0~77.5%, Cr: 18.0~24.0%, Fe: 2.0~10.0%, Nb: 1.20~2.40%, Ti: 0.080~0.300%, and other impurity elements ≤0.50%.

[0007] Based on the total weight of the drug coating, the composition of the drug coating, by weight percentage, is as follows: calcium carbonate: 24-32%; barium carbonate: 8-15%; strontium fluoride: 14-20%; potassium cryolite: 3-8%; sodium cryolite: 5-9%; sodium carbonate: 0.5-1.0%; manganese silicon alloy: 2.8-6.6%; titanium aluminum alloy: 1.2-3.8%; nickel magnesium cerium alloy: 5-8%; molybdenum powder: 5.4-10.8%; silica powder: 2-6%; zircon sand: 2-6%; alginate: 0.8%-2.5%.

[0008] The composition of the weld metal of the nickel-saving LNG storage tank welding electrode, by weight percentage, is as follows: C: 0.05-0.08%; Si: ≤0.25%; Mn: 2.0-2.8%; P: ≤0.005%; S: ≤0.003%; Cr: 12.0-17.0%; Ni: 64-72%; Mo: 3.2-6.0%; Nb: 0.8-2.2%; Al: 0.028-0.080%; Ti: 0.036-0.120%; Fe: 2.4-10.0%.

[0009] The flux coating is uniformly coated onto the core using an adhesive comprising 18-25% of the flux coating weight; the adhesive is sodium silicate with a modulus of 2.6-3.0 and a concentration of 38-42Be.

[0010] The present invention also provides a method for preparing the nickel-saving welding electrode for LNG storage tanks, wherein the nickel-saving welding electrode for LNG storage tanks consists of a welding core and a coating covering the surface of the welding core, and the preparation method is carried out according to the following steps:

[0011] 1) Make the welding core according to the proportions;

[0012] 2) Mix all components of the drug coating evenly according to the specified proportions;

[0013] 3) Add 18-25% of the weight of the coating to the coating, stir and mix evenly, and then use a hydraulic coating machine to evenly coat the coating onto the core wire with a pressure of 8-15 MPa.

[0014] The binder is sodium silicate with a modulus of 2.6 to 3.0 and a concentration of 38 to 42 Be.

[0015] 4) It is baked at high and low temperatures. The low temperature baking temperature is 80~120℃×2h, and the high temperature baking temperature is 350~400℃×1h.

[0016] This invention innovatively develops a low-cost, low-hardness, and easily machinable nickel-chromium-iron welding core. It features an extremely low-carbon, low-Mn, Mo-free, Ni-Cr-Fe, and Ti / Nb-containing composition. The flux coating is designed as a CaCO3-BaCO3-SrF2-crystal slag system, employing a combination of manganese-silicon alloy, titanium-aluminum alloy, and nickel-magnesium-cerium alloy for deoxidation. The welding electrode for nickel-saving LNG storage tanks developed in this invention exhibits excellent all-position welding process performance and good refractory properties. The welding core offers superior economy and machinability. Combined with its unique flux coating design, the welding seam achieves high purity. While maintaining comparable mechanical properties to traditional 9% Ni steel ENiCrMo-6 welding electrodes, it demonstrates better compatibility with newly developed 7% Ni steel for nickel-saving LNG storage tanks. Furthermore, it exhibits superior porosity and crack resistance in thick plate joints. No cracks were observed in bending, positive Y-axis, and oblique Y-axis tests on butt joints, and the TOFD (Total Optical Flaw Detection) pass rate for all-position high-definition radiographic testing reaches over 99.5%.

[0017] This invention features an ultra-low carbon, low Mn, Mo-free, Ni-Cr-Fe, and Ti / Nb composition design. On the one hand, it optimizes the machinability of the welding core, avoids work hardening, simplifies the processing technology, and reduces processing costs. On the other hand, precise control of alloying elements makes the welding metallurgical process more stable, the microstructure more uniform, and the porosity of thick plates better.

[0018] The slag system of this invention is a high-basicity CaCO3-BaCO3-SrF2-crystal slag system. Firstly, it effectively improves the welding characteristics of nickel-based welding electrodes that are prone to red-tailing, and significantly improves the electrode's refractory properties. Secondly, the high proportion of cryolite effectively stabilizes the arc and adjusts the consistency of the slag and molten iron, giving the electrode excellent all-position welding performance while significantly optimizing the porosity resistance of thick plate joints, resulting in a high pass rate for high-definition TOFD flaw detection. The high proportion of F... - It can also maintain the diffusible hydrogen in the weld at an extremely low level. The combination of low-aluminosilicate minerals and a certain proportion of zircon sand can increase the difference in the coefficients of linear expansion between the slag and the molten iron, thereby making it easier for the slag to peel off from the weld and significantly optimizing the slag removal properties of the electrode of this invention.

[0019] This invention designs a deoxidation system that combines manganese-silicon alloy with titanium-aluminum alloy and nickel-magnesium-cerium alloy for deoxidation. From a metallurgical perspective, it fully deoxidizes, removes hydrogen, purifies, removes impurities, and microalloys the weld metal in the molten pool, thereby achieving a perfect combination of high-purity weld and excellent weld metal properties. This results in a uniform weld structure and better porosity and crack resistance in thick plate joints.

[0020] Based on the weight of the coating, the composition and purity of the coating of the welding electrode of the present invention, expressed as a percentage by weight, are as follows:

[0021] Calcium carbonate (CaCO3≥98%): 24-32%;

[0022] Barium carbonate (BaCO3 ≥ 99.5%): 8–15%;

[0023] Strontium fluoride (SrF2 ≥ 99.5%): 14–20%;

[0024] Potassium cryolite (K3AlF6≥99.8%): 3–8%;

[0025] Sodium cryolite (Na3AlF6≥99.5%): 5-9%;

[0026] Sodium carbonate (Na₂CO₃ ≥ 99.8%): 0.5–1.0%;

[0027] Manganese-silicon alloy (Mn≥65%, Si:21-25%): 2.8~6.6%;

[0028] Titanium-aluminum alloy (Ti≥68%, Al: 30~32%): 1.2~3.8%;

[0029] Nickel-magnesium-cerium alloy (Ni / Mg≥85%, Ce:10-15%): 5-8%;

[0030] Molybdenum powder (Mo≥99.8%): 5.4~10.8%;

[0031] Silica powder (SiO2≥99.8%): 2-6%;

[0032] Zircon sand (ZrO2 ≥ 65%, SiO2 30–32%): 2–6%;

[0033] Alginate (pure): 0.8%–2.5%;

[0034] The main functions of the electrode coating of this invention are gas generation, slag formation, improvement of all-position welding processability, deoxidation and micro-alloying, and transition of alloy to the weld. The following is a detailed analysis of the roles played by the main components of the electrode coating in this invention.

[0035] The main functions of carbonates in welding electrodes are slag formation and gas generation. The decomposition produces CaO and BaO, which are alkaline oxides that increase slag basicity, refine molten droplets, and remove sulfur and phosphorus, thus improving the weld metal's crack resistance. They also regulate the slag's melting point, viscosity, surface tension, and interfacial tension. Using a combination of CaCO3 and BaCO3 carbonates at different decomposition temperatures (CaCO3 decomposition temperature 530-900℃, barium carbonate decomposition temperature 800-1450℃) ensures the electrode coating maintains a good protective atmosphere throughout the welding process. The precise combination of minerals with different melting points maintains good refractoriness of the electrode coating. When the carbonate content is low, the coating's gas-generating and slag-forming abilities decrease, reducing its protective effect on the weld and making it difficult to guarantee weld quality. If the carbonate content is too high, the coating generates excessive gas, leading to intense molten pool reaction, increased spatter, higher slag melting point, and rough weld formation. In this invention, the carbonate content is controlled at 32-47%.

[0036] In this invention, the fluorides are mainly SrF2 and cryolite, which can adjust the melting point of the slag and play a key role in reducing weld porosity, improving the physical properties of the slag, and improving weld formation. Because the nickel-based welding rods of this invention have viscous molten iron, high surface tension, and poor fluidity, the weld formation is poor, and gases in the weld are difficult to escape. Cryolite can significantly reduce the surface tension of the molten metal, improve its fluidity, adjust the viscosity of the molten slag, improve slag coverage, resulting in a more aesthetically pleasing weld formation and reducing defects such as porosity. Furthermore, the potassium / sodium cryolite decomposition produces K... + / Na + It can also significantly improve the arc stability of the welding electrode. However, cryolite contains Al, and together with high levels of aluminum oxides and acidic oxides such as SiO2 and TiO2, it easily forms hard and brittle spinel compounds that are difficult to peel off, which seriously affects the slag removal performance. Therefore, the welding electrode of this invention strictly and precisely controls the ratio of cryolite and strontium fluoride, and the total amount of fluoride is controlled at 22-37%.

[0037] To avoid slag adhesion and decreased mechanical properties on the weld surface due to TiO2 and SiO2 inclusions and excessive oxygen content, the flux of this invention contains only a very small amount of silicon micropowder and zircon sand, in addition to the binder water glass. The zircon oxide in the small amount of zircon sand can significantly improve slag removal and avoid the difficulty of slag removal caused by a high proportion of cryolite.

[0038] The main functions of metal powders such as manganese silicon alloy, titanium-aluminum alloy, nickel-magnesium-cerium alloy, and molybdenum powder are deoxidation and microalloying, ensuring the alloy element composition in the weld, ensuring weld strength, and achieving the best balance of strength, toughness, porosity resistance, and crack resistance through reasonable element design. The unique deoxidation system that combines manganese silicon alloy with titanium-aluminum alloy and nickel-magnesium-cerium alloy is an important technical innovation of this invention. Based on the activity of metal elements, the alloy system of this invention ensures that the molten pool is fully deoxidized, dehydrogenated, purified, and impurities removed from the molten pool metallurgy. While achieving excellent weld metal properties, it minimizes Fe intake, ensuring excellent all-position weldability and, more importantly, obtaining better crack resistance and corrosion resistance.

[0039] This invention uses a binder made of pure sodium silicate combined with alginate. Besides coating and bonding the welding rod, the silicate also acts as a slag-forming agent and adjusts the slag state. Pure sodium silicate has better adhesion than potassium silicate, producing a denser and more compact welding rod coating. This allows for a proportional reduction in the amount of silicate used (lower total SiO2 content, preventing excessive silicon penetration into the weld and avoiding slag adhesion due to excessive SiO2). Combined with a precise and reasonable flux formulation design, this results in a better sleeve (Note: the welding rod coating is...). The flux coating melts through heat conduction from the core, so its melting rate lags behind that of the core, forming a "sleeve" around the core. If the flux coating melts too slowly and the sleeve is too deep, it results in poor operability, easy undercut, and a tendency for arc breakage during AC welding. If the flux coating melts too quickly and the sleeve is too shallow, it leads to excessive spatter, poor gas protection, and a high risk of sticking to the plate, affecting welding operation, weld formation, and quality. A uniform and suitable sleeve is crucial for all-position welding. (And with better flux coating refractoriness, the electrode exhibits better all-position weldability and refractoriness.)

[0040] Unlike traditional welding electrodes for 9% Ni steel storage tanks, which generally adopt Ni-Cr-Mo alloy design, the welding electrode of this invention is designed as a Ni-Cr-Fe alloy. It creatively develops a low-cost, low-hardness, easy-to-process, extremely low-carbon, low-Mn, Mo-free, Ni-Cr-Fe, and Ti / Nb-containing nickel-chromium-iron welding core, as well as a CaCO3-BaCO3-SrF2-crystal slag system + manganese-silicon alloy combined with titanium-aluminum alloy and nickel-magnesium-cerium alloy joint deoxidation system.

[0041] ENiCrFe-9 is a nickel-based alloy welding electrode suitable for welding 9Ni steel, but there is currently limited available information and reports on it. Its deposited metal composition is complex, including Cr, Mo, Fe, Mn, Nb, W, and Si in addition to Ni. Strict limits are placed on the C, S, and P contents. Currently, the domestic supply of ENiCrFe-9 welding electrodes for 9Ni steel welding mainly relies on imports, which are expensive. Furthermore, when welding under the medium parameters recommended by foreign manufacturers, the electrode coating turns red-hot, slag removal is difficult, and the tensile strength and low-temperature impact resistance of the deposited metal are low. Porosity is also observed in horizontal and overhead welding of thick plates, all of which negatively impact the mechanical properties of the weld.

[0042] The welding electrode of this invention, through precise design of the above-mentioned composition and proportion, possesses excellent all-position welding performance, stable arc, excellent fire resistance, superior slag removal, and good weld formation. The weld purity is high, exhibiting comparable mechanical properties to the traditional 9% Ni steel ENiCrMo-6 welding electrode, while showing better compatibility with the newly developed nickel-saving LNG storage tank 7% Ni steel. Furthermore, it demonstrates superior porosity resistance and crack resistance in thick plate joints. No cracks were observed in bending, positive Y-axis, and oblique Y-axis tests of the butt joints, and the TOFD (Total Volt Flaw Detection) pass rate for all-position high-definition radiographic testing can reach over 99.5%.

[0043] The beneficial effects of this invention are:

[0044] 1. Low-cost, low-hardness, and easily machinable ultra-low carbon, low-Mn, Mo-free, Ni-Cr-Fe, and Ti / Nb-containing nickel-chromium iron welding cores optimize the machinability of the welding cores, reduce processing costs, and precisely meet the requirements.

[0045] Controlled gold content makes the welding metallurgical process more stable, the structure more uniform, and the porosity better.

[0046] 2. High alkalinity CaCO3-BaCO3-SrF2-crystal slag system, ① significantly improves the refractory properties of welding electrodes;

[0047] ② The high proportion of cryolite in the design gives the welding electrode of this invention excellent all-position welding performance and excellent porosity resistance. The high proportion of F... - It can also maintain the diffusible hydrogen in the weld at an extremely low level; ③

[0048] The combination of low-silica aluminate minerals and a certain proportion of zircon sand can increase the difference in the coefficient of linear expansion between welding slag and molten iron, significantly optimizing the slag removal properties of welding electrodes.

[0049] 3. A deoxidation system combining manganese silicon alloy with titanium-aluminum alloy and nickel-magnesium-cerium alloy is used to fully deoxidize, remove hydrogen, purify, remove impurities and micro-alloy the weld metal from a metallurgical perspective, achieving a perfect combination of high-purity weld and excellent weld metal properties, resulting in uniform weld structure and better joint porosity and crack resistance.

[0050] 4. Using pure sodium silicate combined with alginate as a binder results in better adhesion, reduces the proportion of water glass used, and produces a denser and tighter electrode coating (the total amount of SiO2 is reduced, which can also avoid excessive silicon penetration in the weld and improve the weld slag adhesion caused by excessive SiO2). Combined with a precise and reasonable flux formula design, it can achieve better sleeve and better flux coating refractoriness, and the electrode has better all-position weldability and refractoriness.

[0051] The welding electrode for nickel-saving LNG storage tanks of this invention has excellent all-position welding process performance and excellent fire resistance. The weld purity is high, and the mechanical properties of the deposited metal are excellent and stable. Its tensile strength is ≥700MPa, and its low-temperature impact toughness is excellent. The average impact energy at -196℃ is ≥80J. While having comparable mechanical properties to the traditional 9% Ni steel ENiCrMo-6 welding electrode, it has better compatibility with the newly developed 7% Ni steel for nickel-saving LNG storage tanks on the market. Moreover, it has better porosity resistance and crack resistance in thick plate joints (no cracks were found in the bending, positive Y, and oblique Y tests of the butt joint, and the pass rate of TOFD radiographic testing in all positions can reach more than 99.5%). It can meet the welding requirements of 7% Ni steel for new nickel-saving LNG storage tanks and significantly reduce the construction cost of large LNG storage tanks.

[0052] This invention is applied to the welding of a new type of nickel-saving LNG storage tank. It can give full play to the excellent properties of the base material, greatly improve the safety performance and service life of the nickel-saving LNG storage tank, and has strong practical significance and social value. It will generate huge social and economic benefits. Attached Figure Description

[0053] Figure 1 These are the orthogonal and oblique Y metallographic images of the weld metal crack resistance test in Embodiment 1 of the present invention;

[0054] Figure 2 These are the orthogonal and oblique Y metallographic images of the weld metal crack resistance test in Example 2;

[0055] Figure 3 These are the orthogonal and oblique Y metallographic images of the weld metal crack resistance test in Example 3;

[0056] Figure 4 These are the orthogonal and oblique Y metallographic images of the weld metal crack resistance test in Example 4;

[0057] Figure 5 These are the orthogonal and oblique Y metallographic images of the weld metal crack resistance test in Example 5. Detailed Implementation

[0058] The technical solution of the present invention will be further described below with reference to specific embodiments, but the present invention is not limited to these embodiments.

[0059] This invention consists of a welding core and a flux coating. The flux coating is applied to the outside of the welding core. It innovatively designs and develops a low-cost, low-hardness, easy-to-process nickel-chromium-iron welding core with extremely low carbon, low Mn, no Mo, Ni, Cr, Fe and Ti / Nb composition. The composition of the welding core (weight percentage %) is shown in Table 1.

[0060] Table 1: Core Components (wt%)

[0061] ≤0.01 0.08~0.24 0.60~1.20 ≤0.005 ≤0.003 ≤0.006 Cr Ni Fe Nb Ti Other impurity elements 18.0~24.0 62.0~77.5 2.0~10.0 1.2~2.4 0.080~0.300 ≤0.50

[0062] The core composition of Examples 1-5 is shown in Table 2.

[0063] Table 2: Weld core composition (weight percentage%) for Examples 1-5

[0064]

[0065] The coating of this invention is designed as a high-alkalinity CaCO3-BaCO3-SrF2-crystal slag system + manganese silicon alloy combined with titanium aluminum alloy and nickel magnesium cerium alloy for deoxidation, and the core wire diameter is 2.6mm and 3.2mm.

[0066] The components of the drug coating in Examples 1-5 are shown in Table 3.

[0067] Table 3: Examples of Drug Coating Components (Weight Percentage %)

[0068]

[0069]

[0070] The chemical composition test results of the deposited metal for each implementation case are shown in Table 4.

[0071] Table 4: Chemical composition (wt%) of deposited metal in each implementation case

[0072]

[0073] The mechanical properties, low-temperature impact and crack resistance test results of the weld metals corresponding to each embodiment are shown in Table 5.

[0074] Table 5: Performance of each embodiment

[0075]

[0076] As shown in Table 5, the weld metal deposited by the welding electrode of the present invention has excellent mechanical properties, with a tensile strength ≥700MPa, excellent low-temperature impact toughness, and an average impact energy of ≥80J at -196℃. Figures 1-5These are metallographic images of the weld metal crack resistance tests in Examples 1-5, taken under transverse bending, normal Y-axis, and oblique Y-axis conditions. It is evident that no cracks are visible in the macroscopic metallographic data, and no cracks were found in the transverse bending, normal Y-axis, and oblique Y-axis tests of the butt joints. The weld metal exhibits excellent crack resistance. All-position welding porosity tests, including high-definition radiographic TOFD imaging, showed no porosity.

[0077] As can be seen, the welding electrode of this invention has excellent all-position welding performance, stable arc, excellent fire resistance, and excellent slag removal. The weld purity is high, and the porosity resistance and crack resistance of thick plate joints are superior. No cracks were found in the bending, positive Y, and oblique Y tests of the butt joints, and no porosity was observed in all-position high-definition radiographic testing (TOFD). While possessing comparable mechanical properties to the traditional 9% Ni steel ENiCrMo-6 welding electrode, it exhibits better compatibility with the newly developed nickel-saving LNG storage tank 7% Ni steel, demonstrating excellent joint porosity resistance and bending performance for thick plate base materials.

[0078] This invention is applied to the welding of large LNG storage tanks made of 7% Ni steel for new nickel-saving LNG storage tanks. It can give full play to the excellent properties of the base material, significantly reduce the construction cost of large LNG storage tanks, and at the same time significantly improve the safety performance and service life of cryogenic storage tanks, which has strong economic benefits and social value.

[0079] The embodiments described above are merely preferred embodiments of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the inventive concept of the present invention, and these modifications and improvements all fall within the protection scope of the present invention.

Claims

1. A welding electrode for nickel-saving LNG storage tanks, comprising a core and a flux coating, wherein the flux coating is applied to the outer wall of the core, characterized in that, Based on the total weight of the welding core, the chemical composition and its weight percentage content of the welding core are as follows: C≤0.01%, Mn: 0.60~1.20%, Si: 0.08~0.24%, P≤0.005%, S≤0.003%, P+S≤0.006%; Ni: 62.0~77.5%, Cr: 18.0~24.0%, Fe: 2.0~10.0%, Nb: 1.20~2.40%, Ti: 0.080~0.300%, and other impurity elements ≤0.50%. Based on the total weight of the drug coating, the composition of the drug coating by weight percentage is as follows: calcium carbonate: 24-32%; barium carbonate: 8-15%; strontium fluoride: 14-20%; potassium cryolite: 3-8%; sodium cryolite: 5-9%. Sodium carbonate: 0.5–1.0%; manganese silicon alloy: 2.8–6.6%; titanium aluminum alloy: 1.2–3.8%; nickel magnesium cerium alloy: 5–8%; molybdenum powder: 5.4–10.8%; silicon micro powder: 2–6%; Zircon sand: 2~6%; Alginate: 0.8%–2.5%.

2. The welding electrode for nickel-saving LNG storage tanks according to claim 1, characterized in that, The composition of the weld metal of the electrode, by weight percentage, is as follows: C: 0.05–0.08%; Si: ≤0.25%; Mn: 2.0–2.8%; P: ≤0.005%; S: ≤0.003%; Cr: 12.0–17.0%; Ni: 64–72%; Mo: 3.2–6.0%; Nb: 0.8–2.2%; Al: 0.028–0.080%; Ti: 0.036–0.120%; Fe: 2.4–10.0%.

3. The welding electrode for nickel-saving LNG storage tanks according to claim 1, characterized in that, The flux coating is uniformly coated onto the core using a binder comprising 18-25% of the flux coating weight; the binder is sodium silicate with a modulus of 2.6-3.0 and a concentration of 38-42Be.

4. The welding electrode for nickel-saving LNG storage tanks according to claim 1, characterized in that, The nickel-saving welding electrode for LNG storage tanks consists of a welding core and a coating covering the surface of the welding core, and is prepared according to the following steps: 1) Make the welding core according to the proportions; 2) Mix all components of the drug coating evenly according to the specified proportions; 3) Add 18-25% of the weight of the coating to the coating, stir and mix evenly, and then use a hydraulic coating machine to evenly coat the coating onto the core wire with a pressure of 8-15 MPa. The binder is sodium silicate with a modulus of 2.6 to 3.0 and a concentration of 38 to 42 Be. 4) It is baked at high and low temperatures. The low temperature baking temperature is 80~120℃×2h, and the high temperature baking temperature is 350~400℃×1h.

Citation Information

Patent Citations

  • Two-phase stainless steel electrode

    CN102233489A

  • Nickel-based welding rod for welding nickel, chrome and iron alloy steel

    CN102922169A